The Character Analysis in Ernest Hemingway s Novel The Old Man and The Sea - Muh. Al Fachrizah Fitra; Muh. Soghirun; Nurul Hikmah Ramadhani (Journal of English Language Teaching, Literature and Culture, 2024)
This study examines the characteristics of the major and minor characters in Ernest Hemingway s novel The Old Man and the Sea Employing a qualitative descriptive design the research delves into the portrayal of human traits through the novel s characters The findings reveal that Hemingway skillfully encapsulates various human qualities and struggles in his characters Santiago the protagonist embodies perseverance and resilience despite facing prolonged adversity going eighty four days without catching a fish His eventual capture of the Marlin a massive eighteen foot long fish represents not just a personal victory but also the relentless struggle against forces beyond his control as he ultimately loses the Marlin Manolin a minor character is depicted as a loyal and compassionate boy who supports and cares deeply for Santiago Their bond is marked by mutual respect and a shared passion for baseball highlighting themes of mentorship friendship and intergenerational connection Through these characters Hemingway portrays the universal human experience of determination loss and the enduring strength of relationships < em>< p>